Influence of diet and postmortem ageing on oxidative stability of lipids, myoglobin and myofibrillar proteins and quality attributes of gluteus medius muscle in goats - Adeyemi, Kazeem Dauda; Shittu, Rafiat Morolayo; Sabow, Azad Behnan; Ebrahimi, Mahdi; Sazili, Awis Qurni (Public Library of Science, 2016)
This study appraised the effects of dietary blend of 80% canola oil and 20% palm oil and postmortem ageing on oxidative stability, fatty acids and quality attributes of gluteus medius (GM) muscle in goats. Twenty-four Boer bucks were randomly allotted to diet supplemented with 0, 4 and 8% oil blend, fed for 100 days and slaughtered, and the GM muscle was subjected to a 7 d chill storage (4±1°C). Diet had no effect (P> 0.05) on the colour, drip loss, thiobarbituric acid-reactive substances (TBARS) value, free thiol, carbonyl, myoglobin and metmyoglobin contents, metmyoglobin reducing activity (MRA), antioxidant enzyme activities and abundance of myosin heavy chain (MHC) and actin in the GM muscle in goats. The meat from goats fed 4 and 8% oil blend had higher (P< 0.05) concentration of α and γ-tocopherol and abundance of troponin T compared with that from the control goats. The GM muscle from the oil-supplemented goats had lower (P< 0.05) concentration of C16:0 and greater (P< 0.05) concentration of C18:1n-9, C18:3n-3 and C20:5n-3 compared with that from the control goats. Nonetheless, diet did not affect (P< 0.05) the total fatty acid in the GM muscle in goats. Regardless of the diet, the free thiol and myoglobin contents, concentration of tocopherol and total carotenoids, MHC and MRA in the GM muscle decreased (P< 0.05) while carbonyl content, TBARS, drip loss and metmyoglobin content increased over storage. Dietary blend of 80% canola oil and 20% palm oil beneficially altered tissue lipids without hampering the oxidative stability of chevon.